Inspired by lipids: the Morton Lecture Award Presentation. (15th April 2017) - Harwood, John L.
Abstract : Lipids are key molecules for membranes, energy storage and signalling. I have been privileged to have worked in such a diverse field and in organisms from microbes to humans. Here I will describe some of those contrasting areas which range from environmental impacts to food production and on to human health. It has been a fascinating journey which still continues to excite me.